“Pulpit power” and the unrelenting voice of Archbishop David Gitari in the democratisation of Kenya, 1986 to 1991 (Historia, 2021)
This article sets out to analyse the role of pulpit preaching in the struggle towards the re-emergence of multi-party democracy in Kenya. It argues that through "pulpit power", certain clerics, notably David Gitari, Alexander Muge, Henry Okullu and Timothy Njoya, initiated a process of transformation as individual activists at a time when the state had effectively silenced voices that demanded political change. It then moves on to chronicle David Gitari's sermons as a case in point to demonstrate that his political sermons promoted a culture of defiance in the country and marked the genesis of the so called "second liberation" in Kenya. It relies on archival sources and correspondence material as well as a number of searching in-depth oral interviews.
Keywords: David Gitari; clergy; Daniel arap Moi; political sermons; democracy in Kenya; Anglican Church